Impact of acute versus prolonged exercise and dehydration on kidney function and injury. Issue 11 (11th June 2018) - Bongers, Coen C. W. G.; Alsady, Mohammad; Nijenhuis, Tom; Tulp, Anouk D. M.; Eijsvogels, Thijs M. H.; Deen, Peter M. T.; Hopman, Maria T. E.
Abstract: Exercise and dehydration may be associated with a compromised kidney function and potential signs of kidney injury. However, the kidney responses to exercise of different durations and hypohydration levels are not yet known. Therefore, we aimed to compare the effects of acute versus prolonged exercise and dehydration on estimated glomerular filtration rate (eGFR) and kidney injury biomarkers in healthy male adults. A total of 35 subjects (23 ± 3 years) were included and invited for two study visits. Visit 1 consisted of a maximal cycling test. On Visit 2, subjects performed a submaximal exercise test at 80% of maximal heart rate until 3% hypohydration. Blood and urine samples were taken at baseline, after 30 min of exercise (acute effects; low level of hypohydration) and after 150 min of exercise or when 3% hypohydration was achieved (prolonged effects, high level of hypohydration). Urinary outcome parameters were corrected for urinary cystatin C, creatinine, and osmolality. Subjects dehydrated on average 0.6 ± 0.3% and 2.9 ± 0.7% after acute and prolonged exercise, respectively ( P  < 0.001). The eGFRcystatin C did not differ between baseline and acute exercise (118 ± 11 vs. 116 ± 12 mL/min/1.73 m 2, P  = 0.12), whereas eGFRcystatin C was significantly lower after prolonged exercise (103 ± 16 mL/min/1.73 m 2, P  < 0.001). We found no difference in osmolality corrected uKIM1 concentrations after acute and prolonged exercise ( P  > 0.05), and elevated osmolality corrected uNGAL concentrations after acute and prolonged exercise (all P ‐values < 0.05). In conclusion, acute exercise did barely impact on eGFRcystatin C and kidney injury biomarkers, whereas prolonged exercise is associated with a decline in eGFRcystatin C and increased biomarkers for kidney injury. Abstract : The aim of this study was to compare the effects of acute versus prolonged exercise and dehydration on estimated glomerular filtration rate (eGFR) and kidney injury biomarkers in healthy male adults. We found that acute exercise did barely impact on eGFR and kidney injury biomarkers, whereas prolonged exercise is associated with a decline in eGFR and increased biomarkers for kidney injury.